The Agronomic efficiency of the inoculant FT10 (Trichoderma asperelloides) on four lettuce varieties - Senger, Marina; Moresco, Eloir; Henrique Briega, Anderson; Harakava, Ricardo; Mantovanello Lucon, Cleusa Maria (Comunicata Scientiae, 2022)
The present study aimed to evaluate the agronomic efficiency of FT10 (Trichoderma asperelloides) on lettuce varieties development and productivity throughout the year. Four greenhouse experiments were carried out to verify the effect of three doses of the bio-product on plant growth and yield on loose-leaf, butterhead, iceberg and salad bowl cultivars. A randomized block design was used, with six replications. The treatments were: 1) control, 2) 30.0 x 1012 CFU.ha-1 of the commercial inoculant ICB Nutrisolo ® Trichoderma, 3) 5.0 x 1011 CFU.ha-1 of FT10 inoculant, 4) 10.0 x 1011 CFU.ha-1 of FT10, and 5) 15.0 x 1011 CFU.ha-1 of FT10. Plant dry weight and yield were evaluated 42 DAT. The data obtained were compared with Duncan’s test. Significant increases in yield in up to 21% for loose-leaf and 16% for butterhead were observed with the dose of 15.0 x 1011 CFU.ha-1 and 22% for iceberg and salad bowl with the dose of 10.0 x 1011 CFU.ha-1 of FT10. It can be concluded that FT10 has the potential to promote plant growth and increase the productivity of lettuce cultivars if applied the appropriate dose of the product.